ADVANCED TREATMENT OF FORMATION WATERS FROM THE OIL INDUSTRY TO MITIGATE CORROSION (LACCEI, 2024)
Corrosion in pipelines and metallic components translates into high maintenance costs in the oil industry, reaching a loss of USD 7,000 million annually. One of the leading causes of corrosion occurs due to the contact of formation water with potentially aggressive physicochemical characteristics (high concentrations of salts, chlorides, calcium, and sodium) with metallic surfaces, which, when not treated, produce intragranular corrosion, exfoliation, pitting, and cracks. The latter is considered one of the most dangerous due to its occurrence in inconspicuous areas. This work aims to reduce the concentration of salts in the formation water resulting from hydrocarbon operations in the Ancon field, Santa Elena, Ecuador, by applying two advanced water treatments: electrocoagulation and reverse osmosis. The results showed that the electrocoagulation system is unsuitable for treating this formation water with high electrical conductivity (30 mS/cm) due to the low removal efficiency of approximately 1%. On the contrary, the reverse osmosis system decreased the salt concentration by 84.7% on average, with an energy consumption of 4.95 kWh/m3 and a water recovery of 18% with a single brackish water membrane. Through simulation, the reverse osmosis system was optimized to improve the system's energy efficiency to produce water free of corrosion precursors.